Bridging the Targeting Gap : Assessing Humanitarian Beneficiaries’ Likely Eligibility for Social Protection in Iraq - Phadera, Lokendra; Sharma, Dhiraj; Wai-Poi, Matthew; Douglas, Lotti; Jovanovic, Vladimir; Westerman, Oliver; Khan, Safwan Aziz (World Bank, Washington, DC, 2022)
In Iraq, the Multi-Purpose Cash Assistance programs have been instrumental in reaching the households most affected by the conflict with the Islamic State of Iraq and the Levant in areas where the coverage of the government’s social safety net (SSN) programs remain limited. In the evolving context, however, short-term Multi-Purpose Cash Assistance programs will require eventual integration in some form with the government’s social safety net programs to continue reaching vulnerable households affected by the conflict. As an initial step, this paper proposes an analytical pseudo-proxy-means test (PPMT) tool to bridge the targeting differences between the government’s cash transfer program and the humanitarian Multi-Purpose Cash Assistance programs. Using the common proxies between the cash transfer targeting formulas of the humanitarian agencies and the government, the pseudo-proxy-means test provides each Multi-Purpose Cash Assistance beneficiary’s probability of being eligible for the government’s cash transfer program under different expansion scenarios. When applied to the existing humanitarian beneficiary database, the results of the pseudo-proxy-means test tool suggest the potential for both significant referral numbers and a sequenced referral strategy.